Corrosion of cast iron pipelines buried in Fraser River silt subject to climate-induced moisture variations - Azoor, Rukshan; Asselin, Edouard; Deo, Ravin; Kodikara, Jayantha; Wijewickreme, Dharma (Acta geotechnica, 2021)
Experiments were carried out to characterise the influence of soil water retention properties on the corrosion of a cast iron specimen buried in Fraser River silt. The corrosion rates were measured at different degrees of saturation using standard corrosion tests, along with separate water retention tests for the Fraser River silt. Building on previous work on this topic, a numerical model solving moisture flow, oxygen diffusion, electrical conductivity and their coupled influence on metallic corrosion in unsaturated soil was developed. The experimental data and preliminary numerical modelling results were then used as inputs to a field-scale numerical model to examine climate-induced moisture migration around a pipeline and the resulting levels of corrosion. The time-dependent corrosion mass loss and the resulting loss in pipe wall thickness of a buried pipeline were modelled, and it was demonstrated that the cyclic climatic variations predominantly perturb the corrosion rates during the initial cycles, and subsequently a gradual corrosion rate arises depending on general climatic conditions. Further analysis of the influence of electrical resistivity on the levels of corrosion revealed that a decrease in resistivity due to effects such as seawater intrusion or naturally saline soils may result in a significant increase in the levels of localised corrosion.